PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN TERHADAP PELAKU TINDAK PIDANA YANG MENYIMPAN PSIKOTROPIKA GOLONGAN IV (Studi Putusan Nomor : 461/Pid.Sus./2023/PN.Tjk) - Febriyanta, Ade Armanda; Seregig, I Ketut (Bahasa Indonesia, 2024)
Social deviance, particularly among adolescents, is often influenced byl the abuse of psylchotropic substances. The use of psylchotropics not in accordance with medical prescriptions and legal regulations is considered abuse. This studyl discusses the judges' considerations in rendering decisions against perpetrators of psylchotropic substance storage offenses under Decision Number: 461/Pid.Sus/2023/PN.Tjk. The methods used are juridical-normative and juridical-empirical approaches, utilizing secondaryl and primaryl data, as well as qualitative analylsis. The results indicate that judges' considerations include juridical aspects such as the indictment, prosecutor's demands, and evidence, as well as non-juridical aspects such as the defendant's attitude and social impact. The causes of these crimes include internal factors such as desires and weak faith, as well as external factors like environment and social interactions. The author recommends that judges consider rehabilitation for psylchotropic substance abusers and enhance law enforcement against psylchotropic drug dealers.